Influence of bamboo fiber and limestone powder on the properties of self-compacting concrete. Issue 1 (1st January 2020) - Ede, Anthony N.; Olofinnade, Oluwarotimi M.; Joshua, Opeyemi; Nduka, David O.; Oshogbunu, Obatarhie A.
Abstract: This paper examines the effect of combined bamboo fibers and limestone powder used as filler material on the fresh, hardened and microstructural properties of self-compacting concrete (SCC). The bamboo fibers of aspect ratio ( l/d ) of 50 and a maximum length of 50 mm was varied in steps of 0.25%, 0.5%, 0.75% and 1% in the SCC mix. While 10% of limestone powder was added as a filler in each of the SCC mix. The workability of the mix was assessed by slump flow test and V-funnel test, while the mechanical properties were assessed by considering the compressive and split tensile strength test after 7, 14 and 28 curing age. All concrete mixes were carried out by following the European Federation for Specialist Construction Chemicals and Concrete (EFNARC) standard, while the microstructure of selected samples was assessed using the Scanning Electron Microscopy (SEM). Test results indicate that fiber addition influences the fresh properties of SCC. Moreover, it was observed that SCC mix containing with fiber content of 0.75% and 0.5% with the inclusion of 10% limestone powder achieved the highest compressive and split tensile strength values of 28.04 MPa and 3.26 MPa, respectively. The result showed an increment of 17.4% and 32% compare to the control mix. Results of SEM showed an improvement in the morphology of the concrete. Hence, bamboo fiber and limestone powder can be sustainably combined to regulate the flow-ability and improving the strength of the self-compacting concrete for local structural construction.